2011
DOI: 10.1590/s0102-695x2011005000121
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of acute toxicity of babassu mesocarp in mice

Abstract: Abstract:The safety of babassu mesocarp (Orbignya phalerata Mart., Arecaceae), which exhibited anti-inflammatory and antithrombotic activities, was evaluated by determining the potential acute toxicity in mice. A lyophilized ethanol extract of babassu mesocarp (BME) was administered to C3H/HePas mice (10/group) in a single dose of 1000, 3000 and 5000 mg/kg, by gavage. General behavior adverse effects and mortality were determined for up to fourteen days. Selected biochemical parameters including glucose, triac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
0
3
0
2
Order By: Relevance
“…34 The in vivo low toxicity of babassu mesocarp extract was proved by oral administration of a single high dose (up to 5000 mg kg −1 ) of babassu mesocarp extract to mice once no alterations were identified at the tissue level or body and organ weight (i.e., glucose, triacyl glyceride, cholesterol, and creatinine). 113 However, some changes in biochemistry levels (i.e., increase in alkaline phosphatase and reduction in urea) with a longlasting effect were observed, which the authors considered to be an accidental finding and unrelated to treatment. 113 In 2017, researchers revisiting Amazonian plants commented that babassu seed oil for dermatologic and cosmetic applications was increasing rapidly in applications such as skin rehydration and soothing; anti-inflammatory, antiaging, and antiparasitic effects; hair care; burn and wound healing; and the amelioration of rosacea and psoriasis.…”
Section: Safety and Toxicological Concernsmentioning
confidence: 99%
“…34 The in vivo low toxicity of babassu mesocarp extract was proved by oral administration of a single high dose (up to 5000 mg kg −1 ) of babassu mesocarp extract to mice once no alterations were identified at the tissue level or body and organ weight (i.e., glucose, triacyl glyceride, cholesterol, and creatinine). 113 However, some changes in biochemistry levels (i.e., increase in alkaline phosphatase and reduction in urea) with a longlasting effect were observed, which the authors considered to be an accidental finding and unrelated to treatment. 113 In 2017, researchers revisiting Amazonian plants commented that babassu seed oil for dermatologic and cosmetic applications was increasing rapidly in applications such as skin rehydration and soothing; anti-inflammatory, antiaging, and antiparasitic effects; hair care; burn and wound healing; and the amelioration of rosacea and psoriasis.…”
Section: Safety and Toxicological Concernsmentioning
confidence: 99%
“…Alguns ensaios em modelos animais foram desenvolvidos para testar a toxicidade aguda de diferentes extratos do mesocarpo, porém dados em organismos inferiores são limitados (BARROQUEIRO et al, 2011;MAIA;RAO, 1989, PINHEIRO et al, 2010SOARES et al, 2021;SILVA et al, 2005). Portanto, esforços também devem ser destinados para o desenvolvimento de mais estudos in vitro para determinação da letalidade e citotoxicidade do EMB, pois desempenham papel importante no entendimento do efeito biológico máximo desejável de produtos naturais, dentro de níveis seguros para consumo a longo prazo (ERNST, 2005;SHARWAN et al, 2015) et al, 2017).…”
Section: Introductionunclassified
“…Besides the cosmetic potential, Babassu oil also demonstrated biological activities. Several studies showed that the oil of the species O. phalerata presented antiinflammatory activities, healing (9)(10)(11) and antithrombotic activity (12). In addition, a study was performed to evaluate the safety of unrefined Babassu oil by oral administration to hamsters.…”
Section: Introductionmentioning
confidence: 99%
“…Além do potencial cosmético, o óleo de Babaçu também demonstrou atividades biológicas. Diversos estudos mostraram que o óleo da espécie O. phalerata apresentou atividades anti-inflamatória, cicatrizante (9-11) e atividade antitrombótica (12). Além disso, um estudo unrefined Babassu oil can be a safe source of lipids (5).…”
Section: Introductionunclassified